(3GdJjSjQ aj GdbQGAGJ GdSHYs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdOhGe GdeJWhd HGdEfYGe s
(3BNQgG (B:s
(3aGYde Pdc ehabkG dWQjb GdMb hefgGL GdUhGH Ef TGA Gddg , hHGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3fSNI Ghdis
(3haj hSWgG ChQGb bdjdI HNW MOjK s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs